Author Response: Blood-Brain Barrier Permeability in Patients With Reversible Cerebral Vasoconstriction Syndrome Assessed With Dynamic Contrast-Enhanced MRI. (1st March 2022) - Chen, Shih-Pin; Wang, Shuu-Jiun; Wu, Chia-Hung
Abstract : We thank Dr. Gupta for the comment on our article. 1 We agree with the notion that the brain permeability assessed with dynamic contrast-enhanced MRI at 11.4 ± 8.3 days of disease onset could not completely reflect the true pathogenesis of thunderclap headaches. However, we do believe an enhanced brain microvascular permeability may contribute to the subsequent sensitization of trigeminovascular nociceptors 2, 3 and potentially reflect the dysfunction of neurovascular units. 4 We agreed that the white matter hyperintensities (WMHs) may result from different etiologies generally, but in reversible cerebral vasoconstriction syndrome (RCVS), the dynamics are parallel to the disease course. 5 The discovery of the significantly higher WMH K trans both longitudinally and cross-sectionally may indicate potential causative regional microvascular compromise. In addition, we did not evaluate the postpartum RCVS specifically in this study. The exploratory analysis of the correlation of permeabilities and the clinical parameters was not significant.